Development and validation of valganciclovir hydrochloride in bulk and pharmaceutical dosage form by HPTLC method - K, Karthik; Gnana Babu C, Jose; H.G, Sowmya (International Journal of Advanced Chemistry, 2020)
A simple, rapid and accurate High performance thin layer chromatography is described for the Development and validation of HPTLC method for Valganciclovir Hydrochloride in bulk and Pharmaceutical dosage form. The separation is carried out on Merck TLC aluminum sheets of silica gel 60 F254 using Chloroform: Methanol: Ammonia (6.5:3.4:0.1v/v) mobile phase. Quantification was done by Densitometric scanning at 254nm. The linearity was found to be the range of 100-500ng/spot for Valganciclovir hydrochloride with the correlation coefficient of 0.9993. The regression equation was found to be Y=10.168x-94.8. The Rf value of Valganciclovir hydrochloride was found to be 0.74. The LOD and LOQ were found to 9.19 and 27.87 respectively. Average recovery was found to be 99.66% which show that the method was free from interference from excipients present in the formulation. Simultaneously the Percentage relative standard deviation was well within the range of 2%. The above method was validated according to the ICH guidelines. The established method enabled accurate, precise and applied to the analysis of Valganciclovir hydrochloride in bulk and Pharmaceutical dosage form.Â Â